Trichoderma harzianum in the management of root rot and blight of okra - M.A. AJAYI, D.B. OLUFOLAJI*, M.E. UDOH and (Indian Phytopathology, 2017)
Okra is an important vegetable rich in essential vitamins and iodine in human diet. However, okra production in Nigeria is severely affected by root rot and blight. The efficacy of T. harzianum as seed treatment in the management of root rot and blight of okra was tested. The antagonist inhibited the mycelial growth of M. phaseolina in all the treatments. Significantly (P< 0.05) highest inhibition of 92.11% was recorded in 72 hours and the least in curative having 14.97% at 72 hours. In in-vivo studies, seed germination of 76.90% recorded in T72M Â was significantly the highest. Highest disease incidence of 70.25% was significantly higher in seeds treated with pathogen alone. There was no significant difference in the number of flowers produce by the treatments. Also, it was observed that okra seeds treated with T72M Â had significantly highest number of pods. The result revealed that the use of T. harzianum would be more beneficial, environment friendly in okra cultivation and may be used as an alternative to synthetic fungicides to enhance plant growth and reduce disease incidence, resulting in high okra yield in Nigeria.